The Fund's Response to the 2007-08 Financial Crisis : Stocktaking and Collaboration with the Financial Stability Forum. (Policy Papers; Policy Paper ;, 2008)
The present financial crisis is testing the resilience of the global financial system as well as the robustness of national and multilateral policy frameworks. As requested by Executive Directors, this paper reviews recent progress in meeting these challenges, focusing on the role of the Fund and its collaboration with the Financial Stability Forum (FSF).aIn concert with other international bodies, the Fund has sought to promote appropriate policy responses to the financial turmoil, including through its report on The Recent Financial Turmoil-Initial Assessment, Policy Lessons, and Implications for Fund Surveillance, in the Global Financial Stability Report (GFSR) and the World Economic Outlook (WEO), as well as in recent Article IV consultations and Financial Sector Assessment Programs (FSAPs). The Fund has also responded to the International Monetary and Financial Committee's (IMFC) call for closer collaboration with other international fora, including by supporting the implementation of policy lessons from the crisis, such as the 67 FSF recommendations issued in April 2008.